Pre-release assessment of Javan Gibbon (Hylobates moloch) during acclimatization phase in Mount Malabar Protected Forest, West Java - Anton Ario; Agus Priyono Kartono; Lilik Budi Prasetyo; Jatna Supriatna (School of Postgraduate Studies, Diponegoro Univer, 2019)
Pre-release aassessment study of Javan gibbon (Hylobates moloch) in gradually during acclimatization phase in the Mount Malabar Protected Forest, West Java. We studied eleven Javan gibbons in February-March 2014, February-March 2015, March-April 2015, and July-August 2016. The purpose of this study was to assess the readiness of Javan gibbon behavior in acclimatization phase prior to release. Data collection was conducted by focal animal sampling method with 5-minute interval recording time and ad libitum method. The average time allocation of Javan gibbon activities were the following: feeding 16.82±1,28%; moving 20.01±3.14%; resting 47.64±1.31%; socializing 12.88±2.92%; sexual 0.69±0.54%; and vocalizing 1.96±0.59%. We compared activity allocation data from this study and those from wild Javan gibbons and found similarities as follows: 55.30% at a family of Jowo-Bombom-yani-Yudi, 51.42% at a pair of Moly-Nancy, 44.57% at a pair of Robin-Moni and 62.19% at a family of Mel-Pooh-Asri. Based on readiness assessment of 11 Javan gibbons, 3 were considered almost ready for release, while 8 individuals were considered ready.